2018
DOI: 10.1108/el-01-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Publishing research in the international context

Abstract: Purpose The purpose of this paper is to report the findings of a study to explore the Egyptian social science scholars’ academic writing behaviour in local and international context. Understanding the challenges that scholars in social science and humanities face while publishing in the international outlets would help to suggest strategies to improve academic writing in non-Arabic journals. Design/methodology/approach This study deployed mixed methods approach. The quantitative data were collected using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The participants pointed out that travelling abroad helped them to build scholarly contacts at the international level, which at some point led to working with those contacts on research projects. These results are consistent with the literature on the topic, which found that Egyptian scholars who collaborated in research projects with international peers had travelled abroad and had good English skills (Shehata & Eldakar, 2018).…”
Section: Scholarly Collaborationsupporting
confidence: 91%
See 4 more Smart Citations
“…The participants pointed out that travelling abroad helped them to build scholarly contacts at the international level, which at some point led to working with those contacts on research projects. These results are consistent with the literature on the topic, which found that Egyptian scholars who collaborated in research projects with international peers had travelled abroad and had good English skills (Shehata & Eldakar, 2018).…”
Section: Scholarly Collaborationsupporting
confidence: 91%
“…Many studies have mentioned the same issues (Al-Wreikat et al, 2015;Elgllab & Shehata, 2017 ;Shehata & Eldakar, 2018); however, no efforts are being undertaken to overcome this issue.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations